Analysis of PEST Questionnaire Responses in Patients with Psoriasis in Daily Practice: Results from a Single-Center of Psoriasis in the Czech Republic - Tivadar, Simona; Hugo, Jan; Fuzesiová, Kristína; Doležal, Tomáš; Turková, Barbora; Gkalpakiotis, Spyridon (Dermatology and therapy, 2025)
INTRODUCTION: Psoriatic arthritis (PsA) affects 10-30% of individuals with psoriasis. Early detection of PsA is crucial to prevent potential irreversible joint damage. The Psoriasis Epidemiology Screening Tool (PEST) has proven to be an effective tool in daily clinical practice, but limited data is available on the analysis of positive responses. Our study aimed to determine the combination of positive responses to individual questions and characterize patients with positive PEST results based on specific anatomical sites of psoriasis, duration of the disease, and epidemiological parameters that could potentially predict PEST positivity. METHODS: The PEST questionnaire was randomly administered to patients with psoriasis without psoriatic arthritis attending the outpatient unit for psoriasis treatment. A total of 351 patients completed the PEST questionnaire over a 24-month period. Patients undergoing various types of therapy were included. Each patient completed the PEST questionnaire once, and epidemiological data (such as age, weight, height, body mass index, smoking status, age of disease onset, disease duration, and family history of psoriasis) were collected, as well as types of therapy. RESULTS: We included 242 men and 109 women with an average age of 49.4 years and duration of psoriasis of 23.3 years. A positive PEST questionnaire result was found in 28.5% of patients; 13.1% had a score of 3, 8.0% a score of 4 and 7.4% a score of 5. Nail psoriasis, higher age, and therapy with biological/targeted therapy were associated with PEST positivity. The most frequently observed positive response was nail involvement. CONCLUSION: The PEST questionnaire is a well-established screening tool for identifying patients at risk of having undiagnosed psoriatic arthritis in daily dermatological practice. Patients with nail involvement, higher age, or treated with modern systemic therapy should be closely monitored, as these factors indicate a higher risk of a positive PEST result and consequently higher risk of having psoriatic arthritis.
Keywords: PEST; Psoriasis; Psoriatic arthritis